Pricing of Risk in the Indian Corporate Bond Market: Some Evidence - Shailaja Gajjala (Asian Academy of Management Journal of Accounting and Finance, 2006)
Government bond issues have traditionally dominated primary and secondary Indian debt markets. Corporate bonds account for less than a fifth of outstanding issues. This study is a pioneering effort to identify the determinants of risk premium in the Indian corporate bond market between 1998 and 2002. Results of OLS multiple regression indicate that the factors influencing risk premium differed for institutional and non-institutional trades. The reasons for this are discussed.